The New Approach to the Synoptic Problem - Bultmann, Rudolf (The journal of religion, 1926)
The two-document theory as to the relations of the Synoptic Gospels so generally held twenty years ago has proved to be insufficient to explain the facts. In this article recent developments of synoptic criticism are indicated. The method of investigation, called Formgeschichte, undertakes to discover the various elements in the Gospels by means of typical forms of literary style. On the basis of this study it becomes possible to discover the nature of editorial redaction in the Gospels and to distinguish those portions of the tradition which are original from the secondary elements supplied by the Gospel writers. By comparing the literary styles in the Gospels with parallel literary expressions of Hellenistic and rabbinical literature, light is thrown on the question as to whether a given utterance originated on Palestinian or on Hellenistic soil. It is the conviction of the advocates of formgeschichtliche investigation that this method marks a genuine advance in the task of ascertaining what the historical facts are concerning the preaching of Jesus and the rise of the early Christian community.